2004
DOI: 10.1158/1078-0432.ccr-04-1002
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis to Identify Breast Cancer Biomarkers in Nipple Aspirate Fluid

Abstract: Purpose: Proteomic analysis of breast nipple aspirate fluid (NAF) holds promise as a noninvasive method to identify markers of breast cancer. The objectives of the study were to: (a) describe the NAF proteome, (b) identify candidate markers of breast cancer in NAF by using proteomic analysis, and (c) validate the markers identified by using a quantitative, high-throughput ELISA analysis.Experimental Design: For proteome analysis, NAF proteins from a single subject without breast cancer were separated by two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 28 publications
(21 reference statements)
5
100
1
2
Order By: Relevance
“…PIP has previously been explored as a NAF‐derived biomarker of breast cancer by proteomics and ELISA methods, and expression found to correlate with pre‐/postmenopausal status and cancer stage 33.…”
Section: Resultsmentioning
confidence: 99%
“…PIP has previously been explored as a NAF‐derived biomarker of breast cancer by proteomics and ELISA methods, and expression found to correlate with pre‐/postmenopausal status and cancer stage 33.…”
Section: Resultsmentioning
confidence: 99%
“…However, as we omitted samples that were obviously red from our analyses, we considerably reduced the possibility that the hemoglobin identified in our screen was an artifact. In addition, Alexander et al (2004) found the level of hemoglobin b-chain isoforms to be associated with breast cancer in nipple aspirate fluid, which is normally free of blood contamination. As biochemical modifications of the membrane of erythrocytes in women with ovarian cancer may increase susceptibility to hemolysis of red blood cells, a-and b-hemoglobin have been considered as potential markers for ovarian cancer (Kopczynski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have described in situ and/or infiltrating ductal carcinoma and compared them with normal tissues or non-malignant tumors (64 -71). These approaches have also been applied to biological fluids including serum (72) and nipple aspirate fluids (NAFs) (73). Although 2D electrophoresis has excellent resolution, the requirement for subsequent protein staining and sample handling limits the exhaustivity, sensitivity, and reproducibility of the approach.…”
Section: Mass Spectrometry-based Approachesmentioning
confidence: 99%